Asymmetric silane reduction of ketones and β-Keto esters catalyzed by a chiral azolium/iridium system in the presence of a base in methanol at room temperature - Toshiya Matsuki; Hiro Teramoto; Ryo Ichihara; Kazuo Inui; Satoshi Sakaguchi (Results in Chemistry, 2022)
Asymmetric silane reduction of ketones catalyzed by a system comprising a chiral azolium salt 1 and [Ir(cod)2]BF4 (2) in the presence of a base in methanol was achieved at room temperature within 2 h. Implementing a “pre-mixing” experimental procedure improved the efficiency of the catalytic reaction. Specifically, after treating a mixture of 1 and 2 with (EtO)2MeSiH (3a) in THF, the ketone substrate was allowed to react in the presence of K2CO3 in methanol at room temperature to afford the corresponding optically active alcohol in high yield and enantioselectivity. The reaction parameters were fully evaluated. The presence of 3a in the pre-mixing step and that of a base in the reduction step were found to be essential for success. The developed method was applied to the stereoselective reduction of β-keto esters. Additionally, an iridium species derived from the reaction of 1 with [IrCl(cod)]2 and AgBF4 was investigated.